Religion and Development - Haynes, J. author. aut Link
VII, 250 p.
Keywords: Jeffrey Haynes adopts a chronological and conceptual approach to introduce students to the central themes and theoretical perspectives in the study of religion and development in the developing world, focusing on key themes including environmental sustainability, health and education.